C-Reactive Protein (hsCRP), Diet, and Physical Activity in Rural Women - Margaret Pribulick; Pamela Stewart Fahs; Gale Spencer; Theresa N. Grabro; Steve Wiitala (Online Journal of Rural Nursing and Health Care, 2013)
Purpose: The purpose of this study was to evaluate the effect of dietary fruit and vegetable intake and physical activity (PA) levels on inflammatory marker high sensitivity C-reactive protein (hsCRP) among rural women 35-65 years of age. Sample: Rural, non-smoking women (N = 99) in two states. Method: Cohort analysis from a primary study with randomized-controlled trial (RCT). Results: The dependent variable was calculated as: (a) the log-transformed (log) hsCRP difference, post minus pre values and (b) post log hsCRP. There was no difference between the intervention groups on log difference hsCRP (t (97) = -.88, p = .38); however, those women in the experimental group had half the level of log hsCRP. There was a significant difference in log hsCRP difference by activity level (F (2, 90) = 3.67, p = .03) indicating higher activity reduced hsCRP. Those women with a moderate activity level in the experimental group had the lowest hsCRP levels. The log hsCRP difference was not significantly different when evaluated for those who increased or did not increase their fruit and vegetable intake (p = .35). When analyzed by body mass level there was a significant difference in log hsCRP difference (F = 2.96, 7, 47, p = .001). A multiple regression with three variables accounted for 12% of the variance in log hsCRP. Conclusion: Cardiovascular health of rural women is an area of great concern but limited research. The results of this study indicate increased levels of PA and fruit and vegetable intake by rural women are associated with decreased levels of hsCRP and thus with improved cardiovascular health. This study can contribute to the body of knowledge concerning the role of diet and physical activity on cardiovascular health in rural female populations.